Risk Assessment and Risk-Driven Testing First International Workshop, RISK 2013, Held in Conjunction with ICTSS 2013, Istanbul, Turkey, November 12, 2013. Revised Selected Papers - Bauer, Thomas; Großmann, Jürgen; Seehusen, Fredrik; Stølen, Ketil; Wendland, Marc-Florian (Programming and Software Engineering, 2014)
This book constitutes the thoroughly refereed conference proceedings of the First International Workshop on Risk Assessment and Risk-driven Testing, RISK 2013, held in conjunction with 25th IFIP International Conference on Testing Software and Systems, ICTSS 2013, in Istanbul, Turkey, in November 2013. The  revised full papers were carefully reviewed and selected from 13 submissions. The papers are organized in topical sections on Risk Analysis, Risk Modeling, and Risk-Based Testing.